Use of FT-Raman Spectroscopy to Determine the Degree of Polymerization of Dental Composite Resin Cured with a New Light Source - Khalil, Safaa K.H; Allam, Mousa A; Tawfik, Wael A (European Journal of Dentistry, 2007)
Objectives: To use the FT-Raman spectroscopy for evaluation the degree of polymerization of dental composite as a result of photo curing with a new light source in comparison to the conventional halogen light.Materials and Methods: In this study a new light source, based on a metal-halide lamp (TOPSPOT G12) was developed at NRC-Egypt for curing dental composites. Two groups of 108 composite samples each were cured using both the new light source and a conventional halogen source, as a control source. Different samples’ sizes (2x2, 3x3 and 6x3 mm2) were cured for different periods of time (2, 4, 8, 12, 20, and 40 seconds). The spectroscopic data were analyzed statistically by ANOVA and Duncan’s multiple range test (P< .05).Results: The results showed that the samples cured by the new metal-halide source produced higher polymerization rates than those cured by the halogen source. The polymerization rate was directly proportional to the exposure time and inversely proportional to the sample size, irrespective to the light source used. The results also showed that 12 seconds of metal-halide light curing produced polymerization rate comparable to or even higher than that produced by 40 seconds halogen light curing.Conclusions: The new light source produced a satisfactory degree of polymerization in a remarkable shorter curing time and it can be recommended for clinical use. (Eur J Dent 2007;2:72-79)
Keywords: FT-Raman spectroscopy; Degree of polymerization; Dental composite resin